Fifty years of paracetamol (acetaminophen) poisoning: the development of risk assessment and treatment 1973–2023 with particular focus on contributions published from Edinburgh and Denver - Bateman, D. Nicholas; Dart, Richard C.; Dear, James W.; Prescott, Laurie F.; Rumack, Barry H. (Clinical toxicology (Philadelphia, Pa.), 2023)
Fifty years ago, basic scientific studies and the availability of assay methods made the assessment of risk in paracetamol (acetaminophen) poisoning possible. The use of the antidote acetylcysteine linked to new methods of risk assessment transformed the treatment of this poisoning. This review will describe the way in which risk assessment and treatments have developed over the last 50 years and highlight the remaining areas of uncertainty. A search of PubMed and its subsidiary databases revealed 1,166 references published in the period 1963-2023 using the combined terms "paracetamol", "poisoning", and "acetylcysteine". Focused searches then identified 170 papers dealing with risk assessment of paracetamol poisoning, 141 with adverse reactions to acetylcysteine and 114 describing different acetylcysteine regimens. To manage the extensive literature, we focused mainly on contributions made by the authors during their time in Edinburgh and Denver. The key relationship between paracetamol dose and toxicity risk was established in 1971 and led to the development of the Rumack-Matthew nomogram from data collected in Edinburgh. A series of papers on the mechanisms of toxicity were published in 1973, and these showed that paracetamol hepatotoxicity was caused by the formation of a toxic intermediate epoxide metabolite normally detoxified by glutathione but which, in excess, was bound covalently to hepatic enzymes and proteins. An understanding of the relationship between the rate of paracetamol metabolism, paracetamol concentration, and toxic hazard in humans soon followed. These discoveries were followed by the testing of a range of sulfhydryl-donors in animals and "at risk" patients. Acetylcysteine was developed as the lead intravenous antidote in the United Kingdom. The license holder in the United States refused to make an intravenous formulation. Thus, oral acetylcysteine became the antidote trialed in the United States National Multicenter Study. Intravenous acetylcysteine regimens used initially in the United Kingdom and subsequently in the United States used loading doses of 150 mg/kg over 15 minutes or one hour, 50 mg/kg over four hours, and 100 mg/kg over 16 hours. These regimens were associated with adverse drug reactions (nausea, vomiting and anaphylactoid reactions) and hence, treatment interruption. Newer dosing regimens now give loading doses more slowly. One, the Scottish and Newcastle Anti-emetic Pretreatment protocol, using an acetylcysteine regimen of 100 mg/kg over two hours followed by 200 mg/kg over 10 hours, has been widely adopted in the United Kingdom. A cohort comparison study suggests this regimen has comparable efficacy to standard regimens and offers opportunities for selective higher acetylcysteine dosing. No dose-ranging studies with acetylcysteine were done, and no placebo-controlled studies were performed. Thus, there is uncertainty regarding the optimal dose of acetylcysteine, particularly in patients ingesting very large overdoses of paracetamol. The choice of intervention concentration on the Rumack-Matthew nomogram has important consequences for the proportion of patients treated. The United States National Multicenter Study used a "treatment" line starting at 150 mg/L (992 µmol/L) at 4 hours post overdose, extending to 24 hours with a half-life of 4 hours, now standard there, and subsequently adopted in Australia and New Zealand. In the United Kingdom, the treatment line was initially 200 mg/L (1,323 µmol/L) at 4 hours (the Rumack-Matthew "risk" line). In 2012, the United Kingdom Medicines and Healthcare products Regulatory Agency lowered the treatment line to 100 mg/L (662 µmol/L) at 4 hours for all patients, increasing the number of patients admitted and treated at a high cost. Risk assessment is a key issue for ongoing study, particularly following the development of potential new antidotes that may act in those at greatest risk. The development of biomarkers to assess risk is ongoing but has yet to reach clinical trials. Even after 50 years, there are still areas of uncertainty. These include appropriate acetylcysteine doses in patients who ingest different paracetamol doses or multiple (staggered) ingestions, early identification of at-risk patients, and optimal treatment of late presenters.